An analysis of pancreas transplantation outcomes based on age groupings – an update of the UNOS database. (28th July 2014) - Siskind, Eric; Maloney, Caroline; Akerman, Meredith; Alex, Asha; Ashburn, Sarah; Barlow, Meade; Siskind, Tamar; Bhaskaran, Madhu; Ali, Nicole; Basu, Amit; Molmenti, Ernesto; Ortiz, Jorge
Abstract Introduction Previously, increasing age has been a part of the exclusion criteria used when determining eligibility for a pancreas transplant. However, the analysis of pancreas transplantation outcomes based on age groupings has largely been based on single‐center reports. Methods A UNOS database review of all adult pancreas and kidney‐pancreas transplants between 1996 and 2012 was performed. Patients were divided into groups based on age categories: 18–29 (n = 1823), 30–39 (n = 7624), 40–49 (n = 7967), 50–59 (n = 3160), and ≥60 (n = 280). We compared survival outcomes and demographic variables between each age grouping. Results Of the 20 854 pancreas transplants, 3440 of the recipients were 50 yr of age or above. Graft survival was consistently the greatest in adults 40–49 yr of age. Graft survival was least in adults age 18–29 at one‐, three‐, and five‐yr intervals. At 10‐ and 15‐yr intervals, graft survival was the poorest in adults >60 yr old. Patient survival and age were found to be inversely proportional; as the patient population's age increased, survival decreased. Conclusion Pancreas transplants performed in patients of increasing age demonstrate decreased patient and graft survival when compared to pancreas transplants in patients <50 yr of age.